Effect of Venturi-Shaped Roof Angle on Air Change Rate of a Stairwell in Tropical Climate / Lip Kean Moey ...[et al.] - Lip, Kean Moey; Adam, Nor Mariah; Ahmad, Kamarul Arifin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The objective of this study is to investigate the effect of venturi-shaped roof angle on air change rate (ACH) of a stairwell. Computational Fluid Dynamics (CFD) analysis was conducted to perform the analysis of ACH of a stairwell in a tropical educational institution. A geometrical representation of the experimental dimension was recreated in the CFD simulation. The experimental investigation was carried out using an open circuit low speed wind tunnel for validation purpose. Two k-ε turbulent models were evaluated namely RNG k-ε model and standard k-ε model. It was found that RNG k-ε model closely resembled the trend of those obtained from wind tunnel experiments. Good correlation between the numerical and experimental results was observed (less than 8% average difference). Furthermore, it was found that when the roof angle increased from 40˚ to 50˚, the average ACH was increased by 72%. It was also observed that the indoor speed at level 4 dropped for roof angle below 23˚. This certainly is an indicator to promote more studies to investigate the roof design configuration for better natural ventilation into buildings, which is in line with Malaysia's government vision of sustainable energy for all and a greener Malaysia.